Exploring Complexities of Forgiveness in Religious Traditions in a Post-Conflict Setting: Interviews with Muslim and Christian Leaders in Bosnia and Herzegovina - Stipe Odak (Religions)
This article explores religious understandings of interpersonal forgiveness in post-conflict contexts. It challenges views that portray religious perspectives as purely normative, prescriptive, and insensitive to life’s complexities. This study draws from 75 in-depth interviews with religious leaders from Bosnia and Herzegovina’s three largest faith communities (Islamic Community, Roman Catholic Church, and Serbian Orthodox Church). Using grounded theory methodology for data collection and analysis, this research reveals three interrelated conceptualizations of forgiveness: (1) forgiveness as a dispensation from justified punishment, (2) forgiveness as an emotional process, and (3) forgiveness as a spiritual transformation. This paper further examines forgiveness along the dimensions of procedurality, collectivity, conditionality, and memory. Forgiveness emerges as a fragmented, non-linear process shaped by both individual and collective factors. While some fundamental openness toward forgiveness is often seen as unconditional, its progression depends significantly on the wrongdoer’s actions and broader context. Finally, the findings show that forgiveness does not imply forgetting, yet it substantially influences how past injuries are remembered and commemorated.